Study of the possibility of improving the differentiation of latent and active tuberculosis infection - Zyifi Kadimova (Academy of Sciences of Moldova, 2019)
Latent TB infection (LTI)-asymptomatic nontransmissiv tuberculosis infection with hidden persistence of M.tuberculosis in host organism. The problem of detection of latent tuberculosis infection is very urgent and difficult task. 140 individuals suspected of tuberculosis were examined using conventional clinical and laboratory methods of examination, setting skin immunological reactions to detected delayed hypersensitivity- tuberculin skin test (TST) and Diaskintest (DST). All the patient underwent determination of total antibodies to M.tuberculosis by ELISA. According to the data of examination 97 individuals were found to have latent tuberculosis infection and 43-different forms of pulmonary tuberculosis. Based on the results of the study it can be agued that: 1) The use of DST allows more accurately differentiate latent tuberculosis infection and its activation. 2) Detection of total antibodies to MBT in the range 0,14-2,28 UOD is typical for persons with latent tuberculosis infection. 3) Determination of anti-TB antibodies and their level by ELISA can serve as an additional criterion for the diagnosis of tuberculosis and determine the activity of tuberculosis infection.4) With the exception of the local form of tuberculosis, persons with positive DST, with the level of anti-TB antibodies in the range 0,14-2,28 UOD and with the syndrome of General disorders should be considered as patients with a borderline condition who need preventive anti - tuberculosis chemotherapy.